Theoretical Framework of the Effect of Extrinsic Rewards on Individual’s Attitude Towards Knowledge Sharing and the Role of Intrinsic Attributes - Amin, A.; Hassan, M.F.; Ariffin, M.; Rehman, Mobashar (2009)
Importance of knowledge sharing in Knowledge Management can be denoted as a blood circulating in the body. Theory of Reasoned Action (TRA) is one of the social science theories which are vastly used to understand human behavior and is also considered as a strong base to understand knowledge sharing behavior. Hence this study will use the same theory to understand individual’s knowledge sharing behavior and specifically how extrinsic rewards can affect knowledge sharing attitude. Hence the objective of this study is to propose a framework of individual’s knowledge sharing attitude by using literature from different sources. The study will also propose five hypotheses based on the proposed framework. The study will examine (1) the effect of extrinsic rewards on knowledge sharing attitude (2) How demographic variables effect the relationship between extrinsic rewards and knowledge sharing attitude? (3) What is the effect of OCBs on the effect of extrinsic rewards on knowledge sharing attitude? (4) What is the impact of employee’s knowledge sharing attitude on his/her intention towards knowledge sharing? And (5) what is the impact of employee’s knowledge sharing intention on his knowledge sharing behavior? This will help us to understand how extrinsic motivation influence an individual’s knowledge sharing attitude and how his intrinsic attributes strengthen or weaken this relationship.